Improved define-measure-analyze-improve-control methodology for process improvement in semiconductor industry - Ong, Siew Ying (2014)
In today’s semiconductor industry, many researches have been done to investigate the procedure on problem solving, but still maintain high accuracy in order to keep the customer satisfied. In the past three years, Company A has been rated as “A” supplier from the top customers. Unfortunately, due to recent quality issues on Company A, few customers raised red alerts and quality excursions to Company A for immediate improvement to increase the quality level. Therefore, it is a must for Company A to utilize a best problem solving tool which is more effective and efficient to solve the problem as soon as possible. There are two major techniques chose in most of the Malaysia companies to improve internal defects and external customer complaint, which are Define-Measure-Analyze-Improve-Control (DMAIC) and Eight Discipline (8D). By comparing these two methodologies, there are still rooms for improvement for these two methodologies to reduce lead time as well as the quality of the solution. Current DMAIC structure is rather focusing of improvement projects than on problems that appear ad-hoc. Therefore, the effectiveness of DMAIC structure can be further improved in order to fit all the possible situations. The objectives of this project is first to investigate the effectiveness of DMAIC methodology used for problem solving in semiconductor industry and secondly is to develop a new improved DMAIC methodology to be used in semiconductor industry. Thirdly, the objective to validate the new improved DMAIC methodology in wire bond process. In this research, gaps of DMAIC methodology were studied and questionnaire survey instrument was used to collect the inputs on the process improvement methodology from seven semiconductor companies in Malaysia. There were total 98 respondents of executive levels (managers, senior engineers and junior engineers) participate in the survey. Based on the result from the survey, it is proven that majority of the respondents agreed that containment action is not a comparable explicit step in the DMAIC process and majority of the respondents also agreed that there is weakness or limitation of the DMAIC methodology. In this circumstances, there are high numbers of the employees would like to apply if there is further enhancement of the DMAIC methodology. As a result, a new improvement DMAIC methodology has been developed which includes the Eight Disciplines (8D) inside the DMAIC- DMAIC Plus 8D with enhancement of containment action and best practice sharing. The author has also added the element of formally informed the team, project closure and cascade the improvements to all other relevant products within the enterprise. Lastly,a validation has been done with a case study tested in wire bond process to assess the new improved DMAIC methodology effectiveness. It is proven that with this new systematic approach, all the aspects of customer satisfaction and quality improvement can be achieved. The availability of containment action can avoid the defects escape to the customer and gain customer satisfaction. In a nutshell, this improved DMAIC methodology is a proven approach to achieve the next level of zero defects in all semiconductor industry.